2019
DOI: 10.1096/fj.201802663r
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin‐induced cardiomyocyte death is mediated by unchecked mitochondrial fission and mitophagy

Abstract: Doxorubicin (Dox) is a widely used antineoplastic agent that can cause heart failure. Dox cardiotoxicity is closely associated with mitochondrial damage. Mitochondrial fission and mitophagy are quality control mechanisms that normally help maintain a pool of healthy mitochondria. However, unchecked mitochondrial fission and mitophagy may compromise the viability of cardiomyocytes, predisposing them to cell death. Here, we tested this possibility by using Dox‐treated H9c2 cardiac myoblast cells expressing eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 47 publications
7
117
0
Order By: Relevance
“…As a starting point, initial proof-of-concept experiments were undertaken in rat H9c2 cardiomyocytes 20 , a low-cost, tractable model used most typically in toxicology research and early-stage cardiac drug discovery. Notably, this body of work includes more than 300 studies of anthracycline toxicity [21][22][23][24][25][26][27][28][29][30][31][32][33][34] as well as high-throughput, phenotypedriven screens for novel cardioprotective agents 35,36 . Viability as measured by the CellTiter-Glo ATP generation assay was markedly impaired by DOX, with half-maximal effects at 150-250 nM at 24 and 48 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a starting point, initial proof-of-concept experiments were undertaken in rat H9c2 cardiomyocytes 20 , a low-cost, tractable model used most typically in toxicology research and early-stage cardiac drug discovery. Notably, this body of work includes more than 300 studies of anthracycline toxicity [21][22][23][24][25][26][27][28][29][30][31][32][33][34] as well as high-throughput, phenotypedriven screens for novel cardioprotective agents 35,36 . Viability as measured by the CellTiter-Glo ATP generation assay was markedly impaired by DOX, with half-maximal effects at 150-250 nM at 24 and 48 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the widely reported utility of H9c2 cells [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] , their applicability as a predictive model in cardiac drug development is compromised by their continuous proliferation, lack of the sodium/calcium exchanger NCX1, lack of beating, and skeletal muscle potential 20,38,39 . Moreover, explicit disparities have been reported in drug effects relating to cardioprotection and cardiotoxicity in this model, compared with human cells 40,41 .…”
Section: Inhibitors Of Map4k4 Confer Protection From Dox In Human Pscmentioning
confidence: 99%
“…Previous analysis showed little changes in Drp1 and more mitochondrial elongation in doxorubicin-treated hearts (Abdullah et al, 2019). It was also suggested that levels of Drp1 and Drp1 Ser 616 phosphorylation were increased following doxorubicin challenge (Xia et al, 2017;Catanzaro et al, 2019). Indeed, these authors went on to reveal elevated mitochondrial autophagy, contributing to mitochondrial dysfunction and doxorubicin toxicity.…”
Section: Discussionmentioning
confidence: 96%
“…Pinocembrins’ cardioprotective potential is further endorsed by its vasorelaxant ( Estrada et al., 2020 ) effects which could aid in the preservation of cardiac function by alleviating cardiac fibrosis and left ventricular dysfunction ( Rasul et al., 2013 ; Borriello et al., 2019 ), which is a hallmark for Dox-induced cardiotoxicity. Literature suggests that H9c2 cells are a suitable model to study the effects of Dox-induced cardiotoxicity in an in vitro setting, as it has been shown that the major adverse effects reported in patients exposed to Doxcan be induced in these cells ( Catanzaro et al., 2019 ; Dallons et al., 2020 ; Faridvand et al., 2020 ; Hu et al., 2020 ). Hence, the objective of the current study was to i) assess the prophylactic effect of Pin against the cardiotoxicity inferred by Dox administration using an H9c2 cardiomyoblast model, as well as ii) to evaluate the effect of Pin on the chemotherapeutic potential of Dox in an MCF-7 breast cancer cell line.…”
Section: Introductionmentioning
confidence: 99%